2022
DOI: 10.3390/cancers15010137
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response and Effects of COVID-19 Vaccination in Patients with Lung Cancer—COVID Lung Vaccine Study

Abstract: Lung cancer patients represent a subgroup of special vulnerability in whom the SARS-CoV-2 infection could attain higher rates of morbidity and mortality. Therefore, those patients were recommended to receive SARS-CoV-2 vaccines once they were approved. However, little was known at that time regarding the degree of immunity developed after vaccination or vaccine-related adverse events, and more uncertainty involved the real need for a third dose. We sought to evaluate the immune response developed after vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…IgG titers were maintained over time with low infection and reinfection rates with a mild clinical course. None of the reports by Valanparambil et al [33], Mack et al [32], and Hernandez et al [28] observed differences in serologic responses as a result of cancer treatment in LC patients, but with significant heterogeneity in treatment modalities, were not necessarily powered to do so.…”
Section: Sars-cov-2 Vaccines Immunogenicity In Patients With Lc or Th...mentioning
confidence: 95%
See 2 more Smart Citations
“…IgG titers were maintained over time with low infection and reinfection rates with a mild clinical course. None of the reports by Valanparambil et al [33], Mack et al [32], and Hernandez et al [28] observed differences in serologic responses as a result of cancer treatment in LC patients, but with significant heterogeneity in treatment modalities, were not necessarily powered to do so.…”
Section: Sars-cov-2 Vaccines Immunogenicity In Patients With Lc or Th...mentioning
confidence: 95%
“…Seven studies included healthy controls (HC) in the study cohorts while two studies [4,28] did not employ controls. Overall, after primary dose vaccination, patients with lung cancer showed lower seropositivity rates compared to healthy controls, and in some cases, a suboptimal response to the vaccine was observed in a certain percentage of lung cancer patients.…”
Section: Sars-cov-2 Vaccines Immunogenicity In Patients With Lc or Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study found that during anti-CTLA4 and anti-PD-1 combination immunotherapy, a lung cancer patient developed cytokine release syndrome due to a new crown vaccination, elevated cytokine levels (IL-6, IL-10, and IFN-g), and grade 2 liver and kidney dysfunction (93). However, Hernandez et al (94) believe that the COVID-19 vaccine is safe for patients with lung cancer, and most patients can generate immunity after the first and second doses, reducing the risk of infection.…”
Section: Potential Immunological Impact Of Covid-19 Vaccine In Lung C...mentioning
confidence: 99%
“…However, Hernandez et al. ( 94 ) believe that the COVID-19 vaccine is safe for patients with lung cancer, and most patients can generate immunity after the first and second doses, reducing the risk of infection.…”
Section: Lung Cancer Patients With Covid-19mentioning
confidence: 99%